Richieste lavorative, significatività percepita del lavoro e intenzione di turnover degli infermieri / ob demands, meaningful work, and turnover intention among nurses - Cortese, Claudio Giovanni; Gatti, Paola; Ghislieri, Chiara (La Medicina del Lavoro, 2014)
Summary «Job demands, meaningful work, and turnover intention among nurses». Background: The shortage of nurses is a worldwide issue. Since turnover intention (TI) is considered one of the major determinants of turnover behaviour, it is essential to look deeper into the way it operates. Objectives: This study uses the job demands-resources model to investigate the TI of nurses, on the one hand looking at the relationship that some demands (workload, emotional dissonance and abusive supervision) have on TI and on the other, investigating the role of a specific resource (meaningful work - MW) in terms of its effect on TI and as a potential moderator of the relationship between each demand and TI. Methods: The research project was carried out in a large hospital in Northern Italy by administering a self-report questionnaire to all nurses; 630 questionnaires were distributed, 423 (67.14%) of which were completed. The statistical analyses were performed with PASW 18. Results: The results highlight a positive relationship between demands and TI and a negative relationship between meaningful work and TI. Moreover, a significant moderating effect of meaningful work on the relationship between emotional dissonance and TI also emerged. No significant moderating effects were found for the relationship between the other two demands and TI. Conclusions: This research allowed us to verify the importance of constructs such as abusive supervision and meaningful work that have not yet been extensively studied, within the context of nursing staff in Italy; it also offered a range of suggestions for organizational developments and for further investigations in this field. Riassunto Introduzione: La carenza di personale infermieristico rappresenta un problema globale. Poiché l’intenzione di turnover (TI) viene considerata una delle principali determinanti dell’abbandono della professione, è importante approfondirne le dinamiche. Obiettivi: La presente ricerca si propone di utilizzare il modello delle richieste-risorse lavorative per indagare la TI del personale infermieristico, da un lato verificando la relazione tra alcune richieste (carico di lavoro, dissonanza emotiva e supervisione abusante) e la TI, dall’altro indagando il ruolo di una specifica risorsa, il meaningful work, in termini di effetto diretto sulla TI e di moderazione sulla relazione tra richieste e TI. Metodi: La ricerca è stata condotta in un ospedale del Nord Italia di grandi dimensioni mediante un questionario self-report somministrato a tutti gli infermieri. Sono stati distribuiti 630 questionari, di cui 423 (67,14%) restituiti interamente compilati. Le analisi statistiche sono state realizzate con PASW 18. Risultati: I risultati evidenziano una relazione positiva tra le richieste considerate e la TI, e una relazione negativa tra il meaningful work e la TI. Inoltre è stata evidenziata una moderazione da parte del meaningful work sulla relazione tra dissonanza emotiva e TI. Nessun effetto di moderazione si è invece riscontrato nei confronti della relazione tra le altre due richieste considerate e TI. Conclusioni: La ricerca ha consentito una prima verifica della rilevanza dei costrutti, finora meno indagati, di supervisione abusante e meaningful work nell’ambito del personale infermieristico in Italia, e ha offerto differenti indicazioni per gli interventi in organizzazione e per future indagini sul campo.